Tunable optical and semiconducting properties of eco-friendly-prepared reduced graphene oxide - Tene, Talia; Jiménez-Gaona, Yuliana; Campoverde-Santos, Diana Katherine; Cevallos, Yesenia; La Pietra, Matteo; Vacacela Gomez, Cristian; Scarcello, Andrea; Straface, Salvatore; Caputi, Lorenzo S.; Bellucci, Stefano (Frontiers in Chemistry, 2023)
Wide bandgap oxidized graphenes have garnered particular interest among the materials explored for these applications because of their exceptional semiconducting and optical properties. This study aims to investigate the tunability of the related properties in reduced graphene oxide (rGO) for potential use in energy conversion, storage, and optoelectronic devices. To accomplish this, we scrutinized crucial parameters of the synthesis process such as reduction time and temperature. Our findings demonstrate that controlling these parameters makes it possible to customize the optical bandgap of rGO within a range of roughly 2.2 eV to 1.6 eV. Additionally, we observed that rGO has strong and superior absorption in the visible region, which is attributable to the existence of OFGs and defects. Notably, our results indicate that the absorption coefficients of rGO are up to almost three times higher (7426 ml mg -1 m -1 ) than those observed in dispersions of exfoliated graphene and graphene oxide (GO). To complement our findings, we employed several spectroscopic and morphological characterizations, including scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD), and electrical measurements. The implications of our results are significant for the development and design of future semiconductors for energy conversion and optoelectronic applications.